Recognition of a new serogroup of Legionnaires disease bacterium. - McKinney, R M (1979)
A strain of the Legionnaires disease bacterium (LDB) that was isolated by Joseph E. McDade from a postmortem lung specimen of a patient with fatal atypical pneumonia at the Veterans Administration Hospital in Togus, Maine was serologically different from 16 other strains of LDB that had been isolated previously from patients in other geographic locations. The serological differences of the Togus isolate were shown in results of direct and indirect fluorescent antibody staining and of immunoelectrophoresis with soluble antigen extracts. Seroconversion for the Togus strain of LDB in acute- and convalescent-phase sera from a second patient with atypical pneumonia at the Veterans Administration Hospital in Togus indicated that this patient had been infected with an LDB that was serologically similar or identical to the Togus isolate. The Togus serogroup of LDB should be considered when performing serological tests for Legionnaires disease.